DAMPAK KNOWLEDGE MANAGEMENT TERHADAP PENINGKATAN KINERJA PEGAWAI PADA PERUSAHAAN HOTEL CILACAP - Linda Perdana Wanti; Inka Putri Cahyanti; Abdul Rohman Supriyono (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
Indonesia has many tourist destinations that can be used to increase regional income. Among them are Teluk Penyu Beach and the tourist area of Benteng Pendem which is in Cilacap Regency. This will also affect the formation of tourism accommodations such as hotels. The purpose of this study is to improve the service of hotel employees who are influenced by the performance of hotel employees, so the purpose of this study is to analyze the effect of knowledge management on improving employee performance. The data used in this study uses employee data and other data taken at the Whiz Cilacap Hotel which is located on Jln. General Soedirman, Cilacap Regency, Central Java. The method used in this study is a quantitative descriptive method with independent variables including team performance (X1), employee empowerment (X2), and training (X3), while the dependent variable is employee performance (Y). The results of this study are that the independent variables have a positive and significant influence/impact on the dependent variable, which means that team performance, employee empowerment and training have a positive effect on improving the performance of Whiz Cilacap Hotel employees.